Role of viral infection in the etiopathogenesis of breast cancer - L. A. Ashrafyan; V. K. Bozhenko; A. V. Slonov; O. A. Ovchinnikova; L. Z. Khunova (Опухоли женской репродуктивной системы)
The viral nature of many female genital cancers is now beyond question; however, the role of viral infection in the pathogenesis of breast cancer (BC) has not been adequately investigated. The paper defines the importance of a number of viruses in the etiopathogenesis of on- cogynecological diseases. It presents the results of examining 60 patients with Stages I-IV BC and 30 patients with fibrocystic mastopathy, in whom the presence of DNA-containing virus genomes in tumor tissue was compared, and the data of polymerase chain reaction study of genital tract smears. It is shown that human papillomaviruses and cytomegaloviruses do not play a fundamental role in the develop- ment of BC; there is no valid evidence for Epstein–Barr virus.